Blood Eosinophil Count as a Predictor of Asthma Exacerbation - Damanik, Rizki amaliah; Pradana, Andika; Pandia, Pandiaman (Journal of Society Medicine, 2025)
Introduction: Asthma is a heterogeneous disease characterized by chronic airway inflammation, where eosinophils play a crucial role. Eosinophil levels are often considered a biomarker for asthma severity and treatment response. However, their relationship with asthma exacerbation severity remains unclear. This study aimed to evaluate the relationship between blood eosinophil levels and the severity of asthma exacerbations in patients at Prof. Dr. Chairuddin P. Lubis USU Hospital. Method: This study employed an analytic observational design with a retrospective cohort approach. Data were collected from 25 asthma patients through medical records, including demographic characteristics, blood eosinophil levels, and asthma exacerbation severity. The relationship between eosinophil levels and exacerbation severity was analyzed using the Whitney test. Results: The majority of asthma patients were in the 26-50 age group (44%) and predominantly female (80%). Most patients had blood eosinophil levels <100 (84%), and severe exacerbations were the most common (72%). Statistical analysis showed no significant relationship between blood eosinophil levels and asthma exacerbation severity (p = 0.976). Conclusion: This study found no significant correlation between blood eosinophil levels and asthma exacerbation severity. Other factors, such as corticosteroid use, delayed immune response, and non-eosinophilic asthma, may influence exacerbation severity. These findings emphasize the importance of a multidimensional evaluation in asthma management, including the identification of different asthma phenotypes to guide more precise treatment strategies.